2012
DOI: 10.1371/journal.pone.0053097
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid- vs. Peptide-Odorants: Responses of Individual Olfactory Receptor Neurons in an Aquatic Species

Abstract: Amino acids are widely used waterborne olfactory stimuli proposed to serve as cues in the search for food. In natural waters the main source of amino acids is the decomposition of proteins. But this process also produces a variety of small peptides as intermediate cleavage products. In the present study we tested whether amino acids actually are the natural and adequate stimuli for the olfactory receptors they bind to. Alternatively, these olfactory receptors could be peptide receptors which also bind amino ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 57 publications
2
13
0
Order By: Relevance
“…Ten images before the onset of stimulus application were taken as control (F 0 ). In accordance with previous publications 2 3 13 16 23 a response was considered significant if three criteria were fulfilled: it had to occur within 10 s after stimulus application, the first two fluorescence values after stimulus arrival at the mucosa, F 1 and F 2 , had to be larger than the maximum of the F 0 values, and F 2 had to be larger than F 1 .…”
Section: Methodsmentioning
confidence: 68%
See 1 more Smart Citation
“…Ten images before the onset of stimulus application were taken as control (F 0 ). In accordance with previous publications 2 3 13 16 23 a response was considered significant if three criteria were fulfilled: it had to occur within 10 s after stimulus application, the first two fluorescence values after stimulus arrival at the mucosa, F 1 and F 2 , had to be larger than the maximum of the F 0 values, and F 2 had to be larger than F 1 .…”
Section: Methodsmentioning
confidence: 68%
“…Odor responses were measured as changes of intracellular calcium concentrations of individual olfactory neurons in vibratome slices of the olfactory organs using Fluo-4/AM as calcium indicator dye, essentially as described previously 2 23 . A mix of thirteen amines (2-Phenylethylamine, tyramine, butylamine, cyclohexylamine, hexylamine, 3-methylbutylamine, N,N-dimethylethylamine, 2-methylbutylamine, 1-formylpiperidine, 2-methylpiperidine, N-ethylcyclohexylamine, 1-ethylpiperidine, piperidine) was used to analyse amine responses, ( cf.…”
Section: Methodsmentioning
confidence: 99%
“…The olfactory system of Xenopus tadpoles shows an exquisite sensitivity to detect amino acids in water, which effectively behave as waterborne odorants (Hassenklöver, Pallesen, Schild, & Manzini, ). Through at least 36 classes of ORNs, Xenopus larvae elaborate a map of odors by activating specific glomeruli projecting to M/T cells (Manzini & Schild, ).…”
Section: Resultsmentioning
confidence: 99%
“…Amino acid is a kind of compound that is highly effective chemosensory stimuli in fish. Behavioral evidence has shown that amino acids are detected by a variety of fish [3] and electrophysiological experiments have proven that amino acids are highly effective stimuli in both olfactory and gustatory systems [4]. Three types of olfactory related receptor have been reported in the olfactory epithelium of fish; they include; Olfactory receptors (OR), Vomeronasal Receptor (VR) and Trace-Amine Associated Receptors (TAAR) [5,6] OR genes are a type of G-protein coupled receptors and they are being expressed in the ciliated sensory neurons.…”
Section: Introductionmentioning
confidence: 99%